PENGARUH KUALITAS PELAYANAN, SUASANA (STORE ATMOSPHERE) DAN PROMOSI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Warung Kopi Tuan Malam di Kota Tegal) - safitri, Rina safitri (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to examine how much the Influence of Service Quality, Atmosphere (Store Atmosphere) and Social Media Promotion on Purchasing Decisions (Case study at a night lord coffee shop in Tegal City). The minimum number of research samples used was 190 respondents. The data collection method used is a survey, this research instrument is a questionnaire. The data analysis method used is descriptive analysis and hypotheses are tested using the Structural Equation Model (SEM) with the Smart-PLS (Partial Least Square) program process. The results of this study show that the variables of Service Quality are significantly positive for purchasing decisions, Store Atmosphere is significantly positive for purchasing decisions and Social Media Promotion is significantly positive for purchasing decisions.